Similarity, Data Compression and a Dead Composer - Koopmans, Jetse; van den Berg, Daan; Zaytsev, Vadim (Student Undergraduate Research E-journal!, 2015)
Domenico Scarlatti (1685-1759) is well-known for his 555 keyboard sonatas. Although his work is greatly revered by many professional musicians, some claim that it does not show any compository development. In this paper, his sonatas are clustered by normalized compression distance (NCD), an algorithmical similarity metric with no musical background knowledge. NCD is rooted in Kolmogorov Complexity (KC), a measure that captures the similarity between any two sonatas in a single number. The results show clusters of similar sonatas and suggest Scarlatti’s work does show compository development, even ‘milestone sonatas’ marking changes in artistic style during his lifetime.